Interação com games como alternativa de reabilitação de pacientes com acidente vascular cerebral - Lucatelli, Verônica (2015)
The use of interactive games is a promising method for the rehabilitation of stroke patients. It is a technology that allows people to interact within a three-dimensional environment, besides being an enjoyable and interactive environment, which can aid in motor recovery of upper limbs in adults with stroke. This was the line of research studied for a master's degree, which led two productions in chapter form. The first, entitled "Bioethical analysis on social inclusion of the elderly by means of information and communication technologies (TIC)" expounded on how TICs can be a mean for the elderly to remain independent, physically and intellectually, through technological tools. The second production, entitled "Rehabilitation in stroke patients: New Perspectives", expounded on the epidemiological aspects of stroke, and also on the consequences generated by this disease, rehabilitation ways, including through games, and imaging methods used in stroke detection. The last production, which originated the article in this dissertation, entitled "Games as a new rehabilitation perspective of stroke patients," was a case study evaluated across, with four patients in which two undergoing conventional physiotherapy, and the other two-held Conventional physical therapy with the addition of therapy with game Xbox 360 with Kinect. The conclusion of this study was that the use of games proved to be such a beneficial strategy as conventional therapy in the rehabilitation of stroke patients. The small sample size may have obscured a potential advantage of games compared to conventional Physiotherapy. This technique, combined with physical therapy, is a promising method in the motor recovery after stroke, it is also an opportune and enriching form of stimulus, not only the physical aspects, but multisensory the patient